Pengaruh Mirror Therapy Terhadap Peningkatan Kekuatan Otot Pada Pasien Post Stroke Di Ruangan Neuro RSUD Prof. Dr. H. Aloei Saboe Kota Gorontalo - Samarang, Safitriyanti; Fadli Syamsuddin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
When a stroke occurs, it can leave residual symptoms, one of which is a decrease in muscle strength and if treatment is not immediately received, this can result in post-stroke patients experiencing permanent weakness and even paralysis due to the decrease in muscle strength, so this condition must be treated immediately. Decreased muscle strength in post-stroke patients, apart from being treated with drug therapy, the action that can be given is mirror therapy rehabilitation exercises using mirrors as a rehabilitation exercise medium. This study aims to determine the effect of mirror therapy on increasing muscle strength in stroke patients in the Neuro Room at Prof. Hospital. Dr. H. Aloei Saboe Gorontalo City. Methods: This research uses quantitative research using a pre-experimental design with a one-group pre-post test design approach. The sample in this study was 15 respondents, the data collection technique was using observation sheets using MMST or Manual Muscle Strength Testing. Data were analyzed using the Wilcoxon statistical test Results: The results of the study showed that 15 respondents before mirror therapy had an average muscle strength of 2.53 with a standard deviation of 0.640 and after mirror therapy had an average muscle strength of 3.53 with a standard deviation of 0.640. The results of the Wilcoxon statistical test obtained a p-value of 0.000 (<0.05) Conclusion: There is an effect of mirror therapy on increasing muscle strength in stroke patients in the Neuro Room at Prof. Hospital. Dr. H. Aloei Saboe Gorontalo City.